The Role of Artificial Intelligence in Banking for Leveraging Customer Experience - Chandrima Bhattacharya; Manish Sinha (Australasian Accounting, Business and Finance Journal, 2022)
Purpose: In light of digital advancements, banks need to create customer experiences that strengthen loyalty and trust. For establishing a strong digital banking base, it is crucial for banks to make their processes efficient and fast. The purpose of the paper is to analyze the efficacy of banking functions on implementing Artificial Intelligence for enhancing customer engagement and improving customer satisfaction. It targets banks in metropolitan cities of India having tech-savvy customers, leading a fast-paced life who desire personalization and expect faultless and seamless services. Methodology: The study focusses on front, middle and back-office banking processes. The data for middle and back-office processes is collected through 10 interviews of senior officials and head of IT team in major banks. Literature review and theoretical research is carried out for various international and Indian banks with respect to the integration of AI to improve customer interactions and internal banking processes. For understanding the front-office user experience with AI-Banking, data has been gathered through a survey regarding usage of Chatbots on online banking platforms. A quantitative analysis using the Relative Importance Index reveals major use-cases ranked by customers. Spearman correlation is applied to find the relationship between the two most popular use-cases. Findings: The research paper reveals banking features integrated with AI. Chatbot use-cases on banking platforms are ranked based on customer experience. It is proved that there is a positive correlation (0.247) between the two most popular use-cases. The paper proposes IT Architecture and best practices for the digital banking sector. Practical/Theoretical implications: Based on the complete picture of AI integration with banking operations, evolving Indian banks could focus on the most popular use-cases to attract customers. A comparison with the features developed for various banks may provide a way for growth in the digital banking sector. The correlation between Chatbot use-cases may benefit the established Indian banks to further expand business. Originality/value: Implementation of AI in banking is identified for Indian Banks. It is proved that if a person uses Chatbot for assistance in customer service, they are likely to use Chatbot for recommendation regarding offers and discounts.
Keywords: Artificial Intelligence; Digital Banking; Chatbots; Customer Experience; India